X3d2pov. traductor of x3d to pov-ray (2006)
High-quality and low-quality interactive graphics represent two different approaches to computer graphics’ 3D object representation. The former is mainly used to produce high computational cost movie animation. The latter is used for producing interactive scenes as part of virtual reality environments. Many file format specifications have appeared to satisfy underlying model needs; POV-ray (persistence of vision) is an open source specification for rendering photorealistic images with the ray tracer algorithm and X3D (extendable 3D) as the VRML successor standard for producing web virtual-reality environments written in XML. X3D2POV has been introduced to render high-quality images from an X3D scene specification; it is a grammar translator tool from X3D code to POV-ray code.